Do the cervical spinal canal dimensions predict pre-myelopathic changes of cervical spinal cord? - a magnetic resonance image study - Smitha S Nair; A S Lakshmi; K B Ushadevi; A K Gupta (Wolters Kluwer Medknow Publications, 2015)
Background and aims: The cervical region is the most mobile portion of the spinal column and it is here that the earliest disc degenerations are encountered. Hence it is of great interest to neurologists and neurosurgeons. Degenerative arthritic changes in the cervical spine secondary to ageing may result in bony and soft tissue overgrowth causing encroachment on the cervical spinal canal resulting in cervical canal stenosis. This may predispose to compressive myelopathy. The study aims to determine the predictability of myelopathy based on the dimensions of spinal canal at the cervical region. Materials and methods: The study included 600 patients who underwent MRI scan of cervical spine in the Department of Imaging Sciences and Interventional Radiology, Sree Chithra Thirunal Institute of Medical Sciences and Technology, Thiruvananthapuram, Kerala. It included patients of different age groups of both sexes who were classified into six groups.Tl weighted axial images were obtained using spin echo sequence. The axial slices were made at the mid vertebral levels from C2-C7 vertebrae. The antero posterior diameters of spinal canal in axial images at mid cervical vertebral levels from C2-C7 were measured. Analysis of data was done by mean, standard deviation, independent sample t test, ANOVA and Chi- square test. Results: The mean anteroposterior diameter of the canal at different cervical vertebral levels decreases as age advances. Thepremyelopathic changes were more in males which may be attributed to change in canal shape. Conclusion: Cervical spinal canal dimensions are useful to predict premyelopathic changes of cervical spinal cord.